Rìšti tipo veiksmažodžių šaknies sandara - Kaukienė, Audronė (Baltistica, 1994)
THE ROOT STRUCTURE OF THE rìša TYPE VERBS The verbs of Lith. rìša, Latv. risu „to tie” type are East Baltic innovation. They are formed by unifying the vowel i in apophonical roots (C)eiC/(C)CiC or (C)CeC/CC (Baltic CiC), e.g. Pr. perrēist: senrists. The roots of historical type (C)CeiC must have been formed from primary basic roots by adding one or two enlargements: Cei/Ci + С or CeC/CC + ei/i + C. The roots of these two historical types (with the root vowel e or ei) are mixed and can be distinguished only etymologically.